Development of sago starch-alginate hydrogels for extrusion-based 3D food printing - Taqdissillah, Doohan; Irsyad, Muhammad; Whulanza, Yudan (Eastern-European Journal of Enterprise Technologies, 2025)
The integration of food-grade starch into 3D printing technologies holds significant potential for creating customized, sustainable, and nutritionally enriched food products. This manuscript explores the development of novel sago starch-alginate food inks, specifically examining their rheological behavior, printability, and application potential for extrusion-based 3D food printing. Indonesia, holding over half the world's sago forests (1.28 million hectares), underutilizes this native staple. However, challenges persist in ensuring structural stability, reproducibility, and functional performance. The primary problem addressed is the identification of suitable hydrogel formulations that achieve both reliable printability and structural integrity post-printing. This study establishes that successful 3D printing of alginate-sago hydrogels requires a critical concentration threshold of 20% alginate/sago formulation. A notable feature is the significant discrepancy between theoretical rheological predictions and experimental outcomes for mid-range composites (e. g., Alg6/Sago6 and Alg8/Sago8), underscoring limitations in current rheological models. Sago starch, with its high amylose content and favorable shear-thinning behavior, offers superior printability and storage performance. While sago incorporation significantly enhances shear-thinning behavior and allows for effective viscosity modulation, storage modulus proved more predictive of printability than viscosity parameters. These findings provide practical insights for optimizing starch in maintaining structural fidelity. A circular and cubical shape of printing with height of 10 cm was reached using the line deposition of around 0.5 mm with 90% accuracy of design pattern